A bang‐bang control based water‐loop heat pump load aggregation method for power levelling dispatch. Issue 3 (14th April 2021) - Si, Chaoran; Wang, Zhen; Ju, Ping; Wu, Hao
Abstract: In this article, a bang‐bang control based water‐loop heat pump (WLHP) load aggregation method is proposed to facilitate its attending demand response service for the purpose of power levelling dispatch. A WLHP aggregation model is first established to determine its power limit, in which a priority list based on the state of temperature (SOT) index for each heat pump unit (HPU) is developed to measure the HPU's power regulation capability. Users' comfort is also well guaranteed by introducing a forced switching rule in the model. The proposed model is then applied for a power levelling dispatch problem with WLHP load and a bi‐section based bang‐bang control algorithm is developed to determine HPUs' ON/OFF states. A microgrid test system including wind and solar generation, WLHP load and a battery storage is used to validate the effectiveness of the proposed method. To further test its robustness, an influence analysis of initial operating conditions such as input power profiles and initial ON/OFF states as well as multiple operating‐condition simulations are both conducted.